PENGARUH CORPORATE GOVERNANCE, LEVERAGE DAN UKURAN PERUSAHAAN TERHADAP TAX AVOIDANCE (Studi Empiris Pada Perusahaan Pertambangan Yang Terdaftar Di Bursa Efek Indonesia (BEI) Periode 2011-2015) - Rika Ayu Permatasari, 13.05.52.0101; Setyowati, Widhy (Students Journal of Accounting and Banking, 2017)
This study aims to examine and provide empirical evidence of the impact of corporate governance proxy for independent board, institutional ownership, and the audit committee, and the size of the company leverage against tax avoidance by companies proxied cash ETR (CETR). The study was conducted on mining companies listed on the Indonesia Stock Exchange in the period 2011-2015 with a sample of 141 companies. The sampling technique isÂ  purposive sampling. Analysis of the data used is multiple linear regression analysis. Test results showed that independent board has significant positive effect on tax avoidance, leverage significant negative effect on tax avoidance, institutional ownership has a positive effect is not significant to tax avoidance, while the size of the audit committee and the company has no significant negative effect on tax avoidance. For further research should add other variables that affect tax avoidance companies such as profitability, tax loss carryforwards, or sales growth.Keywords: Tax Avoidance, Corporate Governance, Leverage, Firm Size